Panel summary: Creating resilient and responsive mental health systems for children, youth and families during and beyond the COVID-19 pandemic in Ontario - Alam, S; Gauvin, Francois-Pierre (My University, 2021)
A thematic summary of what was learned from the citizen panel on creating resilient and responsive mental health systems for children, youth and families during and beyond the COVID-19 pandemic in Ontario, about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: mental health systems; children; youth; families; COVID-19; pandemic; Ontario